Review of José Manuel Camacho Sanabria y Rosalía Chávez Alvarado, Riesgos hidrometeorológicos en el sureste mexicano (Quintana Roo): inundaciones urbanas. México: Universidad Autónoma del Estado de Quintana Roo, 2022 - Alonso Velasco, Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Hydrometeorological risks in southeastern Mexico (Quintana Roo): urban flooding, coordinated by José Manuel Camacho Sanabria and Rosalía Chávez Alvarado, represents a joint effort of students and researchers to provide instruments aimed at better decision-making to prevent and reduce the risk of flood-related disasters in some Quintana Roo cities. The research contained in this work does not only have an academic purpose, but must be considered by the different social and technical sectors involved in risk mitigation. Quintana Roo, due to its geographical location, is an entity that is constantly impacted by climatic systems that cause floods that bring with them numerous damages and economic losses. Despite this, there are no local studies that serve to design strategies and actions aimed at reducing these consequences. That is why this book contains a proposal for the constitution of an Observatory of Resilience to Flood Risk and four case studies in coastal cities of Quintana Roo. The coordinators of this collective work intend to encourage the dissemination and dissemination of studies associated with this subject beyond the Caribbean entity, where this type of hydrometeorological phenomena also occurs.